GAMBARAN GANGGUAN SISTEM MUSKULOSKELETAL PADA FISIOTERAPIS DI KOTA DEPOK - Daffa Amirah Chairunissa (2022)
Musculoskeletal disorders are a group of painful disorders of muscles, tendons, and nerves. They are common causes of severe chronic pain and physical disability. Causes of musculoskeletal disorders can be divided into two, namely individual factors and occupational factors. Musculoskeletal disorders that occur due to work factors can cause WMSDs (work-related musculoskeletal disorder's). WMSDs (work-related musculoskeletal diseases) are one of the most common occupational ailments among healthcare employees around the world. Work-related musculoskeletal disorders (WMSDs) are an important health risk within the physiotherapy profession. Physiotherapy can lead to WMSDs in physiotherapists because of the nature of their profession. There were limited studies carried out regarding musculoskeletal disorders among physiotherapists in Indonesia, particularly in Depok. . Therefore, the aim of this study was to identify and analyze the description of musculoskeletal disorders among physiotherapists in Depok City. The design of this research is a quantitative descriptive study using a survey approach with a questionnaire. The parameter used to measure musculoskeletal disorders in this study was the Nordic Body Map Questionnaire. and the sampling technique was purposive sampling with the samples of 70 physiotherapists in Depok City. Analysis of the data used is univariate analysis. The results showed as many as 70 physiotherapists in Depok City, obtained (97.1%) with a subjective classification of musculoskeletal disorders with a mild risk level, and (2.9%) a moderate risk level. The most frequent complaints of musculoskeletal disorders were in the lumbar region (97.2%), followed by the lower neck (95.7%), and the upper neck (95.7%).